2013
DOI: 10.1111/1365-2435.12143
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of seed dispersal by small rodents: a role for predator and conspecific scents

Abstract: Summary1. Seed-caching rodents play a key role in the ecology of seed dispersal by not only consuming but also dispersing seeds. Rodent foraging behaviour is usually framed within optimal models, which predict that their decisions should maximize food intake and minimize foraging costs. Although predation risk and seed pilferage by conspecifics have been envisaged as two potential costs, their relevance for seed-caching behaviour and seed dispersal has barely been addressed. 2. To test the effect of predation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 64 publications
4
44
0
3
Order By: Relevance
“…Indeed, large rodents from Caviidae and Echimyidae and marsupials from Caluromys genus were the first groups to disappear in the presence of anthropogenic pressure, such as fragmentation and defaunation (Chiarello 1999, Costa et al 2005. Knowing that biodiversity loss is not a random process (Dirzo et al 2014), even for small mammals, there are biased impacts on these species that influence important functions such as seed dispersal and predation (Vieira et al 2003, 2006, Sunyer et al 2013), controlling the seeds reservoir of the forests, as well as in the dispersal of mycorrhizal fungi (Janos andSahley 1995, Mangan andAdler 2002). Phylogenetic and functional diversity are often loosely correlated (Pavoine et al 2013) and has been reported in birds (Trindade et al 2012, Sobral andCianciaruso 2016), large mammals (Safi et al 2011), fish (Cachera and Le Loc'h 2017) and plants (Flynn et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, large rodents from Caviidae and Echimyidae and marsupials from Caluromys genus were the first groups to disappear in the presence of anthropogenic pressure, such as fragmentation and defaunation (Chiarello 1999, Costa et al 2005. Knowing that biodiversity loss is not a random process (Dirzo et al 2014), even for small mammals, there are biased impacts on these species that influence important functions such as seed dispersal and predation (Vieira et al 2003, 2006, Sunyer et al 2013), controlling the seeds reservoir of the forests, as well as in the dispersal of mycorrhizal fungi (Janos andSahley 1995, Mangan andAdler 2002). Phylogenetic and functional diversity are often loosely correlated (Pavoine et al 2013) and has been reported in birds (Trindade et al 2012, Sobral andCianciaruso 2016), large mammals (Safi et al 2011), fish (Cachera and Le Loc'h 2017) and plants (Flynn et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon occurs for example when jays or tree squirrels pilfer and redistribute primary caches made by conspecifics (Vander Wall, , 2002b; Emery & Clayton, ). In fact, intraspecific cache pilfering is not rare among scatter‐hoarding rodents and corvids (Vander Wall, , 2002b; Gerhardt, ), and may have influenced the foraging and caching behaviour of the dispersers and the spatial pattern and dispersal distance of cached seeds (Moore et al ., ; Sunyer et al ., ). Consequently, we presume that many nut‐bearing trees are frequently dispersed both primarily and secondarily by the same species of rodents and birds.…”
Section: The Ecological Relevance Of Synzoochorymentioning
confidence: 97%
“…Carnivores can also have indirect effects on seed dispersal when seed dispersal behavior of the primary disperser (or seed predator) is altered by carnivore presence (Sunyer et al. , Steele et al. ).…”
Section: Implications Of Secondary Seed Dispersal By Carnivoresmentioning
confidence: 99%